Indigenous Peoples' experiences with pharmacy education in Canada - Swidrovich, Jaris (2024)
In my dissertation my concern is the individual and collective experiences of Indigenous Peoples with pharmacy education in Canada. Indigenous Peoples are drastically underrepresented in the pharmacy profession. As an Indigenous (Saulteaux) pharmacy professional myself, I have my own lived and living experiences as an Indigenous person in Canadian pharmacy education and practice that I reflect on with respect to the underrepresentation of Indigenous Peoples in the pharmacy profession; however, there is no available literature regarding the experiences of Indigenous Peoples with pharmacy education in Canada. Following the release of the Truth and Reconciliation Commission of Canada’s Calls to Action in 2015, post-secondary institutions have collectively engaged in decolonization, Indigenization, and reconciliation efforts. To respond to the Calls to Action related to health and education, more Indigenous pharmacy professionals are required. Unfortunately, though, Indigenous representation in the pharmacy profession remains low and with unclear explanations for the continued underrepresentation. This PhD dissertation will, for the first time, examine the holistic experiences Indigenous Peoples have had throughout their first professional degree in pharmacy and offer suggestions for post-secondary pharmacy programs to engage in decolonization, Indigenization, and reconciliation. I passionately share my rationale for why I am doing this work. Literature review findings are shared regarding Indigenous Peoples in pharmacy education and practice. Specifically, the general tensions between Indigenous and Western paradigms are described through a summary of the critiques of Indigenous scholars worldwide. Specific tensions between each paradigm with respect to pharmacy education and practice are also summarized. Limited findings from the literature with respect equity, diversity, inclusion, accessibility, and belonging are also shared. Indigenous methodologies is described and summarized with examples of specific methods, ...